# Given $x^2 + 4x + 6$ as factor of $x^4 + ax^2 + b$, then $a + b$ is [closed]

I got this task two days ago, quite difficult for me, since I have not done applications of Vieta's formulas and Bezout's Theorem for a while. If can someone solve this and add exactly how I am supposed to use these two theorem's on this task, I would be thankful.

Given $x^2 + 4x + 6$ as factor of $x^4 + ax^2 + b$, then $a + b$ is equal to?

## closed as off-topic by Ali Caglayan, colormegone, Mike Pierce, user223391, Claude LeiboviciJun 17 '15 at 8:15

This question appears to be off-topic. The users who voted to close gave this specific reason:

• "This question is missing context or other details: Please improve the question by providing additional context, which ideally includes your thoughts on the problem and any attempts you have made to solve it. This information helps others identify where you have difficulties and helps them write answers appropriate to your experience level." – Ali Caglayan, colormegone, Mike Pierce, Community, Claude Leibovici
If this question can be reworded to fit the rules in the help center, please edit the question.

Since $x^4 + a x^2 + b$ is even (i.e. invariant under $x \to -x$), so is its factorization. If $x^2 + 4 x + 6$ is one factor, the other must be ....

• Top-shelf answer. – Orest Bucicovschi Jun 17 '15 at 7:53
• Let us add an ingredient since more complicated answers might mask it: $x^4+ax^2+b=(x^2+4x+6)(x^2-4x+6)$, plugging $x=1$ yields that $1+a+b$ is $(1+4+6)(1-4+6)=(1+6)^2-4^2$ and $a+b=49-16-1=$ $___$. – Did Jun 20 '15 at 18:05

There is some quadratic $x^2 + cx + d$ such that: $$(x^2 + 4x + 6)(x^2 + cx + d) = x^4 + ax^2 + b$$ Multiply it out: $$x^4 + (c + 4)x^3 + (d + 4c + 6)x^2 + (6c + 4d)x + 6d = x^4 + ax^2 + b$$ Equate coefficients:

$$\begin{cases} c + 4 = 0 \\ d + 4c + 6 = a \\ 4d + 6c = 0 \\ 6d = b \end{cases}$$

Use the first equation to find $c$. Use the third to find $d$. Use those to find $a$ and $b$.

• +1 for converting the polynomial equation into a system of linear equations. You would use the third equation to find $d$. Then the fourth to find $b$, and the second to find $a$. OP, for convenience, here is the equation set arranged as they would be solved via row-reduction. $$\begin{cases} 0a + 0b + c + 0d = -4 \\ -a + 0b + 4c + d = -6 \\ 0a + 0b + 6c + 4d = 0 \\ 0a - b + 0c + 6d = 0 \end{cases}$$ And the solution is: $$a = -4 ~~~ b = 36 ~~~ c = -4 ~~~ d = 6$$ – FundThmCalculus Jun 17 '15 at 1:29

Let $r_1,r_2$ be the roots of $x^2+4x+6$. By Vieta's $r_1+r_2 = -4$ and $r_1r_2 = 6$.

Since $x^2+4x+6$ is a factor of $x^4+ax^2+b$, we have that $r_1,r_2$ are also roots of $x^4+ax^2+b$.

Then, since $x^4+ax^2+b$ is an even polynomial, $-r_1,-r_2$ are also roots of $x^4+ax^2+b$.

It is easy to see that $r_1,r_2,-r_1,-r_2$ are distinct, so we've found all four roots of $x^4+ax^2+b$.

Therefore, $x^4+ax^2+b$ $= (x-r_1)(x-r_2)(x+r_1)(x+r_2)$ $= \left[(x^2-(r_1+r_2)x+r_1r_2\right]\left[(x^2+(r_1+r_2)x+r_1r_2\right]$ $= (x^2+4x+6)(x^2-4x+6)$ $= x^4 - 4x^2 + 36$.

Hence, $a = -4$, $b = 36$, and thus, $a+b = 32$.

Note: I'm not sure how Bezout's Theorem is needed here.

EDIT: Little Bezout's Theorem is also known as the polynomial remainder theorem, which was used above.

• The quotient could also have been simply presented as $(-x)^2 + 4(-x) + 6$, since the roots are reversed, bypass all of vieta's stuff. – DanielV Jun 17 '15 at 5:02

\begin{align*} x^4+ax^2+b & = x^2\color{blue}{(x^2+4x+6)}-4x\color{blue}{(x^2+4x+6)}+\\ &(a+10)\color{blue}{(x^2+4x+6)}-\color{red}{(4a+16)(x)+(b-6a-60)} \end{align*} For $x^2+4x+6$ to divide the given polynomial.We need $4a+16=0$ and $b-6a-60=0$. Thus $a=-4$ and $b=36$.

• This doesn't give the correct answer, probably an arithmetic mistake somewhere. – DanielV Jun 17 '15 at 0:14
• @DanielV you are right I had made an error in the constant coefficient. I have fixed that. Thanks. – Anurag A Jun 17 '15 at 0:34
• I got a positive 36 for b – DanielV Jun 17 '15 at 0:34
• @DanielV sorry I did not erase the $-$ from the previous answer. – Anurag A Jun 17 '15 at 0:35

The first solution I came up with involves actually finding the roots of the quadratic, then employing Factor/Remainder theorem, so while it is a tad more tedious, it's also very direct. I will follow with an alternative solution that is more elegant.

By the quadratic formula, roots of $x^2 + 4x + 6$ are the complex conjugate pair $-2 \pm i\sqrt 2$.

By Factor Theorem, those will also be roots of the quartic (biquadratic), giving the linear simultaneous equations:

$(-2 + i\sqrt 2)^4 + a(-2 + i\sqrt 2)^2 + b = 0$

$(-2 - i\sqrt 2)^4 + a(-2 - i\sqrt 2)^2 + b = 0$

Now $(-2 \pm i\sqrt 2)^2 = 2 \mp 4i\sqrt 2$

Squaring again,

$(-2 \pm i\sqrt 2)^4 = -28 \mp 16i \sqrt 2$

which allows you to express the simultaneous equations as:

$(-28 - 16i\sqrt 2) + a(2 - 4i\sqrt 2) + b = 0$

$(-28 + 16i\sqrt 2) + a(2 + 4i\sqrt 2) + b = 0$

by subtraction, we almost immediately have $a(8i\sqrt 2) = -32i\sqrt 2 \implies a = -4$

By adding and back substitution, we get: $-56 + 4(-4) + 2b = 0 \implies b = 36$

And of course, to answer the original question, $a+b= 32$

Alternative solution:

Let the roots of the original quadratic be $x_1, x_2$.

Vieta's formulas give:

$x_1 + x_2 = -4$

$x_1x_2 = 6$

from which we can deduce that:

$x_1^2 + x_2^2 = (x_1 + x_2)^2 - 2x_1x_2 = 4$

and

$x_1^2x_2^2 = 36$

Now, by Factor Theorem, $x_1$ and $x_2$ are also roots of the biquadratic.

If we let $y = x^2$, the biquadratic can be written as:

$y^2 + ay + b = 0$

which will have roots $y_1$ and $y_2$ where $y_1 = x_1^2$ and $y_2 = x_2^2$

Applying Vieta's formula to the quadratic in $y$ allows us to deduce that:

$y_1 + y_2 = -a \implies x_1^2 + x_2^2 = -a$

and

$y_1y_2 = b \implies x_1^2x_2^2 = b$

and by reference to the above results, that allows us to immediately conclude that $a = -4, b = 36$ and $a+b = 32$.

This solution involves Vieta's formulas, and is less tedious than my original method.

If $x^2 + 4x + 6$ is factor of $x^4 + ax^2 + b$, then it must satify

$$x^4 + ax^2 + b=(x^2 + 4x + 6)Q(x)$$ where $Q(x)$ is a second degree polynominal. You do not need to find $Q(x)$

$x^2 + 4x + 6=0$

$x^2=-(4x + 6)$

$$x^4 + ax^2 + b=(x^2 + 4x + 6)Q(x)$$

$$(-(4x + 6))^2 - a(4x + 6)+ b=0$$

$$16x^2+48x+36 - 4ax -6a+ b=0$$ $$-16(4x + 6))+48x+36 - 4ax -6a+ b=0$$

$$-64x -96+48x+36 - 4ax -6a+ b=0$$

$$-16x -60 - 4ax -6a+ b=0$$

$$-16-4a=0$$

$$a=-4$$

$$-60 -6a+ b=0$$ $$-60 +24+ b=0$$ $$b=36$$

then $a+b=32$